Mild Cognitive Impairment Patients Have Higher Regulatory T-Cell Proportions Compared With Alzheimer's Disease-Related Dementia Patients - Fu, Jiping; Duan, Jinhai; Mo, Jianwei; Xiao, Hao; Huang, Yuedong; Chen, Weiping; Xiang, Shaotong; Yang, Fan; Chen, Yongjun; Xu, Shuwen (Frontiers in Aging Neuroscience, 2021)
Objectives: The role of neuroinflammation in the pathogenesis of Alzheimer's disease (AD) has attracted much attention recently. Regulatory T-cells (Tregs) play an important role in modulating inflammation. We aimed to explore the Treg-related immunosuppression status at different stages of AD. Methods: Thirty healthy control (HC) subjects, 26 patients with mild cognitive impairment (MCI), 30 patients with mild probable AD-related dementia, and 28 patients with moderate-to-severe probable AD-related dementia underwent detailed clinical history taking, structural MRI scanning, and neuropsychological assessment. Peripheral blood samples were taken to measure the percentage of CD4+CD25+CD127low/− Tregs by flow cytometry and the levels of interleukin (IL-10), interleukin (IL-35), and transforming growth factor β (TGF-β) by ELISA. Results: The percentage of Tregs in the blood of MCI patients was the highest (9.24%); there was a significant difference between patients with MCI and patients with probable AD-related dementia. The level of TGF-β in patients with MCI (47.02 ng/ml) was significantly increased compared with patients with AD-related dementia. There were positive correlations between Treg percentage, IL-35, and Mini-mental state evaluation scores in patients with MCI and probable AD-related dementia. Conclusions: Patients with MCI have stronger Treg-related immunosuppression status compared with patients with probable AD-related dementia.